2019
DOI: 10.1039/c9ra07599b
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipid exhibits antifungal activity by ROS mediated endoplasmic reticulum stress and mitochondrial dysfunction pathways in Candida albicans

Abstract: Sophorolipid induces ROS generation in C. albicans leading to mitochondrial dysfunction and ER stress followed by the release of Ca2+ ions (from the ER lumen) that enter mitochondria and further magnify ROS generation leading to cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…As mentioned earlier, the intracellular ROS accumulation leads to fatal consequences such as necrosis, apoptosis and oxidative stress. Necrosis is a form of pathological cell death induced by extreme physical, chemical or other serious pathological stimuli [25,27,28]. In our study, using DCFH-DA and PI double staining method proved that the cell necrosis induced by AMP-17 is associated with the increase of intracellular ROS production.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…As mentioned earlier, the intracellular ROS accumulation leads to fatal consequences such as necrosis, apoptosis and oxidative stress. Necrosis is a form of pathological cell death induced by extreme physical, chemical or other serious pathological stimuli [25,27,28]. In our study, using DCFH-DA and PI double staining method proved that the cell necrosis induced by AMP-17 is associated with the increase of intracellular ROS production.…”
Section: Discussionmentioning
confidence: 50%
“…If the ROS produced by the cell exceeds its metabolic capacity, the excess intracellular ROS induces oxidative damage to lipids, DNA, proteins and other cellular components (such as plasma membrane). The induction of these processes is related to cellular death caused by apoptosis or necrosis [25][26]. This study found that AMP-17 treatment increased the ROS generation and showed a good concentrationdependent effect, but when the C. albicans cells were pretreated with two antioxidants, glutathione, and ascorbic acid, the accumulation of intracellular ROS induced by the AMP-17 in C. albicans was signi cantly inhibited.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations